Non-Enzymatic Oligomerization of 3', 5' Cyclic AMP - Costanzo, Giovanna; Pino, Samanta; Timperio, Anna Maria; Šponer, Judit E; Šponer, Jiří; Nováková, Olga; Šedo, Ondrej; Zdráhal, Zbyněk; Di Mauro, Ernesto (PloS one, 2016)
Recent studies illustrate that short oligonucleotide sequences can be easily produced from nucleotide precursors in a template-free non-enzymatic way under dehydrating conditions, i.e. using essentially dry materials. Here we report that 3',5' cyclic AMP may also serve as a substrate of the reaction, which proceeds under moderate conditions yet with a lower efficiency than the previously reported oligomerization of 3',5' cyclic GMP. Optimally the oligomerization requires (i) a temperature of 80°C, (ii) a neutral to alkaline environment and (iii) a time on the order of weeks. Differences in the yield and required reaction conditions of the oligomerizations utilizing 3',5' cGMP and cAMP are discussed in terms of the crystal structures of the compounds. Polymerization of 3',5' cyclic nucleotides, whose paramount relevance in a prebiotic chemistry context has been widely accepted for decades, supports the possibility that the origin of extant genetic materials might have followed a direct uninterrupted path since its very beginning, starting from non-elaborately pre-activated monomer compounds and simple reactions.
Keywords: Cyclic GMP; Kinetics; guanosinmonofosfát cyklický; Hydrogen-Ion Concentration; koncentrace vodíkových iontů; kinetika; polymerizace; Polymerization